Simultaneous assessment of Lagrangian strain and temperature fields by improved IR-DIC strategy. (July 2017) - Wang, X.G.; Liu, C.H.; Jiang, C.
Abstract: This paper focuses on the development of a novel digital image correlation strategy based on infrared imaging (IR-DIC) for realizing simultaneous assessment of Lagrangian strain and temperature fields. A major difficulty in the IR-DIC is the evolution of the thermal field during deformation that is unexpected in the image correlation. Two solutions are proposed to tackle this difficulty. The first solution is to utilize a high-pass filter to eliminate the variation part of the thermal signal, and the second solution is to employ an advanced metric, the mutual information, as the correlation criterion. Both methods are verified through a tensile test performed on a notched specimen. The estimated displacement and strain fields demonstrate well the desirable performance of the proposed methods. Thanks to the kinematic field assessment, the obtained thermal fields can be described in the Lagrangian coordinate system, thus the temperature evolution of the material points during deformation can be followed effectively. Highlights: Simultaneous Lagrangian strain and temperature field assessment is realized. A dedicated IR-DIC strategy is proposed in utilization of a high-pass filter. Mutual information is applied as the correlation criterion in the IR-DIC. Lagrangian thermal evolution in a heterogeneous deformation is characterized.